Diagnosis dan Penanganan TB-IRIS Paradoksikal: Tinjauan Pustaka - Gotama, Yovita; Suryana, Ketut (Cermin Dunia Kedokteran, 2025)
Tuberculosis (TB) is the most common opportunistic infection in patients with human immunodeficiency virus (HIV). TB-HIV is a global burden, especially in TB endemic countries, such as Indonesia, and increased mortality. Patients with HIV need antiretroviral drugs treatment as early as possible but comorbidity with TB carries a high-risk of immune reconstitution inflammatory syndrome (IRIS), which can worsen clinical condition and increase the mortality rate. TB-IRIS is divided into 2 categories, namely paradoxical TB-IRIS in patients who have previously received TB therapy and unmasking TB-IRIS in patients newly diagnosed with TB after initiation of ARV. Clinical manifestations of TB-IRIS include worsening respiratory and constitutional symptoms, as well as the appearance of new lesions in other organs. The diagnosis of TB-IRIS requires the exclusion of other conditions such as opportunistic infections or TB treatment failure. Prevention strategies include TB screening before ARV initiation, selection of the appropriate timing for ARV administration, and the use of corticosteroids such as prednisone to reduce the risk of worsening. Management of TB-IRIS focuses on supportive therapy, inflammation control, and continuation of ARV and OAT treatment. With early detection, prevention, and appropriate management, morbidity and mortality rates due to TB-IRIS can be significantly reduced.